Release film for ceramic green sheet molding

The mold release film for ceramic green sheets addresses friction-induced electrostatic charging and transport issues by using a polyester base with a controlled antistatic layer, ensuring smoothness and transportability, thus improving the manufacturing process of ultra-thin multilayer ceramic capacitors.

JP7605386B1Active Publication Date: 2024-12-24TOYOBO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024557144
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-30
Filing Date
2024-05-17
Publication Date
2024-12-24
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

Conventional mold release films for ceramic green sheets, particularly those used in manufacturing ultra-thin multilayer ceramic capacitors, suffer from defects such as pinholes and short circuits due to friction-induced electrostatic charging and poor transportability, leading to issues like misalignment of printed electrodes and contamination during the manufacturing process.

Method used

A mold release film with a polyester base material and an antistatic layer containing an antistatic resin and wax, where the release layer has an area surface roughness less than 10 nm and the antistatic layer's roughness is controlled to maintain a specific ratio with the release layer, ensuring balanced antistatic and transport properties.

Benefits of technology

The film effectively suppresses electrostatic charging and friction-induced issues, preventing contamination, misalignment, and pinhole formation, while maintaining smoothness and transportability, thereby enhancing the quality of ceramic green sheet molding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605386000001
    Figure 0007605386000001
  • Figure 0007605386000002
    Figure 0007605386000002
  • Figure 0007605386000003
    Figure 0007605386000003
Patent Text Reader

Abstract

An object of the present invention is to provide a release film for molding ceramic green sheets which satisfies both antistatic performance and film transportability, inhibits the antistatic agent from falling off, and has smoothness. The release film for molding ceramic green sheets comprises, in this order, a release layer, a polyester film as a substrate, and an antistatic layer. The substrate has two surfaces with different roughnesses, the antistatic layer contains an antistatic resin and a wax, the area average surface roughness (Sa1) of the release layer is smaller than 10 nm, and the area average surface roughness (Sa1) of the release layer and the area average surface roughness (Sa2) of the antistatic layer are 0.02
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a release film for molding a ceramic green sheet, and more particularly to a release film used when molding an ultra-thin ceramic green sheet. [Background technology]

[0002] Conventionally, release films having a polyester film as a base material and a release layer laminated thereon have been used as process films for molding ceramic green sheets such as adhesive sheets, cover films, polymer films, and optical lenses.

[0003] The release film is also used as a process film for molding ceramic green sheets that require high smoothness for multilayer ceramic capacitors, ceramic substrates, etc. Ceramic green sheets are molded by applying a slurry containing ceramic components such as barium titanate and a binder resin onto a release film and drying it. The molded ceramic green sheets are printed with electrodes and peeled off from the release film to obtain ceramic green sheets, which are then laminated, pressed, fired, and coated with external electrodes to produce multilayer ceramic capacitors.

[0004] In recent years, as multilayer ceramic capacitors become smaller and have larger capacities, the thickness of ceramic green sheets has also tended to become thinner. In the manufacturing process of thin ceramic green sheets, defects such as pinholes occur due to slight protrusions on the release film during the process of coating and drying the ceramic green sheets on the release film, and short circuits occur in multilayer ceramic capacitors using the ceramic green sheets. For this reason, there is a demand for release films with a smooth release surface on which the ceramic green sheets are coated.

[0005] However, as the release film becomes smooth, the amount of static electricity increases when the film roll is unwound and wound up, posing an operational problem.

[0006] In response to the above-mentioned problems, various efforts have been made to impart antistatic properties to release films for producing ceramic green sheets. Patent Document 1 describes a method of mixing an antistatic component into the release layer itself, while Patent Document 2 describes a method of providing an antistatic layer as an undercoat layer before providing a release layer.

[0007] On the other hand, a technique has been proposed in which an antistatic layer is provided on the surface opposite to the processing surface on which the ceramic green sheet is provided, as in Patent Document 3. Also, Patent Document 4 has been proposed in which an antistatic layer formed on the side opposite to the release layer of a release film contains a cationic polymer compound and a slippage improver. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2011-206996 A [Patent Document 2] JP 2010-155459 A [Patent Document 3] JP 2006-130724 A [Patent Document 4] Japanese Patent Application Publication No. 10-315373 Summary of the Invention [Problem to be solved by the invention]

[0009] In the process of printing electrodes on a molded ceramic green sheet, a process is used in which an electrode paste is screen-printed on the ceramic green sheet surface of a roll-shaped release film with a ceramic green sheet, and then the sheet is continuously put into a dryer to dry and then wound up again into a roll. In this process, the surface opposite to the electrode-printed surface, i.e., the surface of the release film opposite to the processing surface on which the ceramic green sheet is to be provided, comes into contact with a support in the dryer, and the sheet is transported while undergoing friction. This causes various problems, such as the inclusion of foreign matter due to charging caused by friction, and the printing process being shifted due to problems in film transport caused by friction.

[0010] Furthermore, although the techniques described in Patent Documents 1 and 2 are effective in suppressing the generation of static electricity when the ceramic green sheet is peeled off from the release film, they do not take into consideration the generation of static electricity during transportation.

[0011] The techniques of Patent Documents 3 and 4 are effective in terms of antistatic properties, but do not take into consideration the transportability of the release film, and therefore do not solve problems such as deviations in the printing process due to problems with film transport caused by friction. In addition, no consideration is given to the falling off of the antistatic layer due to friction between the antistatic layer and the support in the dryer, which has led to new problems due to the falling off of the antistatic material, etc.

[0012] The present invention has been made in view of the problems of the conventional technology. That is, an object of the present invention is to provide a release film for molding a ceramic green sheet, which has both antistatic performance and film transportability, suppresses the dropping off of the antistatic layer, and has smoothness. [Means for solving the problem]

[0013] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above object can be achieved by a release film having the following configuration, and have completed the present invention.

[0014] That is, the present invention comprises the following: [1] A release film for molding a ceramic green sheet, comprising a release layer, a polyester film as a substrate, and an antistatic layer in this order, The substrate has two surfaces with different roughnesses, the antistatic layer contains an antistatic resin and a wax, The average surface roughness (Sa1) of the release layer is less than 10 nm, and The area surface average roughness (Sa1) of the release layer and the area surface average roughness (Sa2) of the antistatic layer satisfy the following formula: 0.02 <Sa1 / Sa2<0.5 Release film for molding ceramic green sheets. [2] The release film for molding ceramic green sheets according to the above [1], wherein the content of the wax is 1% by mass or more and 60% by mass or less relative to 100% by mass of the total solid content in the antistatic layer. [3] The release film for molding ceramic green sheets according to the above [1] or [2], wherein the wax comprises a polyolefin wax. [4] The release film for molding ceramic green sheets according to any one of the above [1] to [3], wherein the antistatic layer has a thickness of 0.005 to 0.1 μm. [5] The release film for molding a ceramic green sheet according to any one of the above [1] to [4], wherein the antistatic resin is an acrylic resin having a cationic functional group. Effect of the Invention

[0015] The release film for molding ceramic green sheets of the present invention not only has excellent antistatic properties, but also has excellent flatness of the release layer, and therefore can be suitably used for molding ceramic green sheets in the thin layer region. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention can suppress the generation of static electricity due to friction, for example, in a process of printing electrodes on a molded ceramic green sheet, in a state in which the surface of the release film opposite the processing surface where the ceramic green sheet is provided comes into contact with a support in a dryer and the sheet is transported while undergoing friction.

[0017] The present invention can suppress the charge generation during transport, and therefore can suppress the inclusion of foreign matter due to charge generation caused by friction. Furthermore, the transportability is good, and the occurrence of poor winding and wrinkles in the film that may occur during film transport can be suppressed.

[0018] Furthermore, since the present invention has a good balance between good antistatic properties and winding properties, damage to the green sheet during molding of the thin layer region of the ceramic green sheet can be suppressed, and further, displacement of the printed electrodes can be suppressed.

[0019] In addition, the present invention can suppress not only the generation of charge when the ceramic green sheet is peeled off from the release film, but also the generation of charge during transportation.

[0020] Here, the present invention has excellent adhesion between the substrate and the antistatic layer, and can prevent the antistatic layer from falling off due to friction between the antistatic layer and the support in the dryer. In addition, it can suppress process contamination caused by the antistatic resin falling off the antistatic layer and the generation of pinholes in the green sheet, and can also solve new problems caused by the falling off of the antistatic resin.

[0021] The present invention will now be described in more detail.

[0022] [Polyester film] The polyester constituting the polyester film used as the substrate in the release film of the present invention is not particularly limited, and a film formed from a polyester generally used as a substrate for a release film can be used, but it is preferably a crystalline linear saturated polyester consisting of an aromatic dibasic acid component and a diol component, for example, polyethylene terephthalate, polyethylene-2,6-naphthalate, polybutylene terephthalate, polytrimethylene terephthalate, or a copolymer mainly composed of these resin components is more preferable, and a polyester film formed from polyethylene terephthalate is particularly preferable. The polyethylene terephthalate preferably has a repeating unit of ethylene terephthalate of 90 mol % or more, more preferably 95 mol % or more, and may be copolymerized with a small amount of other dicarboxylic acid components and diol components, but from the viewpoint of cost, it is preferable to use one produced only from terephthalic acid and ethylene glycol. In addition, known additives such as antioxidants, light stabilizers, ultraviolet absorbers, and crystallizing agents may be added within a range that does not inhibit the effects of the film of the present invention. The polyester film is preferably a polyethylene terephthalate film because of its high bidirectional elastic modulus.

[0023] The intrinsic viscosity of the polyethylene terephthalate film is preferably 0.50 to 0.70 dl / g, more preferably 0.52 to 0.62 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, breakage is less likely to occur during the stretching process, which is preferable. Conversely, when the intrinsic viscosity is 0.70 dl / g or less, cuttability is good when cutting into a predetermined product width, and dimensional defects do not occur, which is preferable. In addition, it is preferable to thoroughly vacuum dry the raw material.

[0024] The method for producing the polyester film in the present invention is not particularly limited, and a method generally used in the past can be used. For example, the polyester is melted in an extruder, extruded into a film, and cooled on a rotating cooling drum to obtain an unstretched film, which is then uniaxially or biaxially stretched. A biaxially stretched film can be obtained by sequentially biaxially stretching a uniaxially stretched film in the longitudinal or transverse direction, or by simultaneously biaxially stretching an unstretched film in the longitudinal and transverse directions.

[0025] In the present invention, the stretching temperature during stretching of the polyester film is preferably equal to or higher than the second-order transition point (Tg) of the polyester, and the stretching is preferably 1 to 8 times, particularly 2 to 6 times, in both the longitudinal and transverse directions.

[0026] The polyester film preferably has a thickness of 12 to 50 μm, more preferably 12 to 38 μm, and even more preferably 15 to 31 μm. If the film has a thickness of 12 μm or more, it is preferable because there is no risk of deformation due to heat during film production, during the processing step of the release layer, and during molding of the ceramic green sheet. On the other hand, if the film has a thickness of 50 μm or less, the amount of film to be discarded after use is not excessively large, which is preferable in terms of reducing the environmental load, and furthermore, it is preferable from an economical point of view because the material per area of ​​the release film used is reduced.

[0027] The polyester film substrate may be a single layer or a multilayer of two or more layers, but is preferably a laminated polyester film having a flat layer A that does not substantially contain inorganic particles on at least one side. In the case of a laminated polyester film having a multilayer structure of two or more layers, it is preferable to have a lubrication layer that can contain particles on the opposite side of the layer that does not substantially contain inorganic particles. As for the lamination structure, if the layer on the side to which the release layer is applied is the flat layer A, the layer on the opposite side is the lubrication layer, and the other core layer is the core layer, the layer structure in the thickness direction can be a lamination structure such as release layer / flat layer / lubrication layer / antistatic layer, or release layer / flat layer / core layer / lubrication layer / antistatic layer. Of course, the core layer C may be a multi-layer structure. In the polyester film substrate of the present invention, the flat layer A forming the surface to which the release layer is applied is preferably substantially free of inorganic particles. In this case, the area surface average roughness (Sa) of the flat layer A is preferably 10 nm or less. If Sa is 10 nm or less, the film thickness of the release layer is 2.0 μm or less, and even if it is thinner, such as 0.5 μm or less, it is preferable because pinholes and the like are unlikely to occur during molding of the ultra-thin ceramic green sheet to be laminated. It can be said that the smaller the area surface average roughness (Sa) of the flat layer A, the more preferable it is, but it may be 0.1 nm or more. However, when an anchor coat layer or the like described later is provided on the flat layer A, it is preferable that the coat layer does not substantially contain inorganic particles, and it is preferable that the area surface average roughness (Sa) after lamination of the coat layer is within the above range.

[0028] In order to make the present invention easier to understand, the area surface average roughness of the release layer surface of the substrate is sometimes described as (Sa1), but unless otherwise specified, the area surface average roughness (Sa1) means the area surface average roughness of the release layer.

[0029] In the present invention, "substantially free of inorganic particles" is defined as a content of 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit, when inorganic elements are quantified by fluorescent X-ray analysis. This is because even if inorganic particles are not actively added to the film, contaminants derived from foreign matter or dirt attached to the raw material resin or the line or equipment in the film manufacturing process may peel off and be mixed into the film.

[0030] In the case where the polyester film substrate in the present invention is a laminated film, the easy-slip layer forming the side opposite to the flat layer A on which the release layer is applied preferably contains particles, particularly silica particles and / or calcium carbonate particles, from the viewpoint of the slipperiness of the film and ease of air escape. The content of the particles contained is preferably 5000 to 15000 ppm in total in the easy-slip layer. In this case, the area surface average roughness (Sa) of the easy-slip layer is preferably in the range of 1 to 40 nm, more preferably in the range of 5 to 35 nm.

[0031] The present invention has an antistatic layer on the side of the polyester film opposite to the side on which the release layer is provided. Here, when the polyester film has a lubricating layer, the antistatic layer is disposed on the lubricating layer. By making the area surface average roughness (Sa) of the film constituting the lubricating layer within the above range, the average roughness (Ra2) of the antistatic layer can be prevented from becoming excessive.

[0032] In order to make the present invention easier to understand, the area surface average roughness of the surface of the substrate facing the antistatic layer is sometimes referred to as (Sa2); however, unless otherwise specified, the area surface average roughness (Sa2) means the area surface average roughness of the antistatic layer.

[0033] By setting the area surface average roughness (Sa) of the film of the easy-slip layer in the above range, and further, by containing an antistatic resin and a wax in the antistatic layer, the area surface average roughness (Ra2) of the antistatic layer is 0.02 <Sa1 / Sa2<0.5 The relationship expressed as:

[0034] Although not intended to be limited to any particular theory, the synergistic effect of the antistatic resin and wax of the present invention results in the area average surface roughness (Sa2) of the antistatic layer without the surface shape of the polyester film being directly transferred to the antistatic layer.

[0035] As a result, (Sa1 / Sa2) falls within a predetermined range, and the present invention can, for example, provide a good balance between good antistatic properties and winding properties, suppress damage to the green sheet when molding the ceramic green sheet in the thin layer region, and further suppress misalignment of the printed electrodes.

[0036] When the total of the silica particles and / or calcium carbonate particles in the easy-slip layer is 5000 ppm or more and Sa is 1 nm or more, the air can be uniformly released when the film is wound into a roll, and the film has a good rolled appearance and good flatness, making it suitable for producing an ultra-thin ceramic green sheet. Also, when the total of the silica particles and / or calcium carbonate particles is 15000 ppm or less and Sa is 40 nm or less, the lubricant is less likely to aggregate and coarse protrusions are not formed, so that defects such as pinholes do not occur in the ceramic green sheet even when the ultra-thin ceramic green sheet is wound after molding, which is preferable.

[0037] As the particles contained in the easy-slip layer, it is more preferable to use silica particles and / or calcium carbonate particles from the viewpoint of transparency and cost. In addition to silica and / or calcium carbonate, inactive inorganic particles and / or heat-resistant organic particles can be used, and other usable inorganic particles include alumina-silica composite oxide particles and hydroxyapatite particles. In addition, as heat-resistant organic particles, cross-linked polyacrylic particles, cross-linked polystyrene particles, benzoguanamine particles, etc. can be mentioned. In addition, when using silica particles, porous colloidal silica is preferable, and when using calcium carbonate particles, light calcium carbonate that has been surface-treated with a polyacrylic acid-based polymer compound is preferable from the viewpoint of preventing the lubricant from falling off.

[0038] The average particle diameter of the particles added to the easy-slip layer is preferably 0.1 μm or more and 2.0 μm or less, and particularly preferably 0.5 μm or more and 1.0 μm or less. If the average particle diameter of the particles is 0.1 μm or more, the slipperiness of the release film is good, which is preferable. Also, if the average particle diameter is 2.0 μm or less, there is no risk of pinholes due to coarse particles occurring on the surface of the release layer, which is preferable. The average particle diameter of the particles can be measured by observing the particles on the cross section of the processed film with a scanning electron microscope, observing 100 particles, and taking the average value as the average particle diameter. As long as the object of the present invention is satisfied, the shape of the particles is not particularly limited, and spherical particles and irregular non-spherical particles can be used. The particle diameter of the irregular particles can be calculated as the circle equivalent diameter. The circle equivalent diameter is the value obtained by dividing the area of ​​the observed particles by pi (π), calculating the square root, and multiplying it by two.

[0039] The lubrication layer may contain two or more types of particles made of different materials, or may contain the same type of particles with different average particle sizes.

[0040] When the easy-slip layer does not contain particles, it is also preferable to provide the easy-slip layer with a coating layer containing particles. The means for providing this coating layer is not particularly limited, but it is preferable to provide it by the so-called in-line coating method, which is applied during the film formation of the polyester film. In addition, when providing a coating layer that provides easy-slip properties on the surface of the polyester film on the side on which the release layer is not laminated, the polyester film does not need to have a flat layer and an easy-slip layer, and may be made of a single-layer polyester film that does not substantially contain inorganic particles.

[0041] As described later, an antistatic layer may be provided simultaneously with the lubricating coating layer by in-line coating.

[0042] The area surface average roughness (Sa) of the easy-slip layer is preferably 40 nm or less, more preferably 35 nm or less, and even more preferably 30 nm or less. On the other hand, the area surface average roughness of the easy-slip layer needs to be larger than the area surface average roughness of the flat layer, so it is preferably 10 nm or more. In addition, even when the easy-slip layer or the surface of the single-layer polyester film on the side on which the release layer is not laminated is made easy to slip by a coating layer, the Sa of the surface is measured by the surface on which the coating layer is laminated, and it is preferably in the same range as the area surface average roughness (Sa) of the easy-slip layer B. For example, the area surface average roughness (Sa) of the film of the coating layer (easy-slip layer) is 10 nm or more and 40 nm or less, and may be 10 nm or more and 35 nm or less.

[0043] (Coat layer (easy-slip layer)) It is preferable that the coating layer on the surface of the polyester film on which the release layer is not laminated contains at least a binder resin and particles.

[0044] (Binder resin for easy-slip layer) The binder resin constituting the coating layer (easy-slip layer) is not particularly limited, but specific examples of polymers include polyester resin, acrylic resin, urethane resin, polyvinyl resin (polyvinyl alcohol, etc.), polyalkylene glycol, polyalkyleneimine, methyl cellulose, hydroxycellulose, starch, etc. Among these, polyester resin, acrylic resin, and urethane resin are preferably used from the viewpoint of particle retention and adhesion. In addition, polyester resin is particularly preferable when considering compatibility with polyester film. In order to achieve solubility and dispersibility in a solvent, and further adhesion with the base film and other layers, the polyester of the binder is preferably a copolymer polyester. The polyester resin may be polyurethane-modified. In addition, another preferable binder resin constituting the coating layer (sometimes called an easy-slip layer or an easy-slip coating layer) on the polyester base film is urethane resin. As the urethane resin, polycarbonate polyurethane resin is exemplified. Furthermore, polyester resin and polyurethane resin may be used in combination, and the above other binder resins may be used in combination.

[0045] (Cross-linking agent for coating layer) In the present invention, the coating layer may be formed containing a crosslinking agent in order to form a crosslinked structure in the coating layer. By including a crosslinking agent, it becomes possible to further improve adhesion under high temperature and high humidity conditions. Specific examples of the crosslinking agent include urea-based, epoxy-based, melamine-based, isocyanate-based, oxazoline-based, carbodiimide-based, and aziridine-based crosslinkers. In addition, in order to promote the crosslinking reaction, a catalyst or the like can be appropriately used as necessary.

[0046] (Particles in the coating layer) The easy-to-slip coating layer preferably contains lubricant particles to impart slipperiness to the surface. The particles may be inorganic particles or organic particles, and are not particularly limited. Examples of the inorganic particles include (1) silica, kaolinite, talc, light calcium carbonate, heavy calcium carbonate, zeolite, alumina, barium sulfate, carbon black, zinc oxide, zinc sulfate, zinc carbonate, zirconium oxide, titanium dioxide, satin white, aluminum silicate, diatomaceous earth, calcium silicate, aluminum hydroxide, hydrated halloysite, calcium carbonate, magnesium carbonate, calcium phosphate, magnesium hydroxide, and barium sulfate, and (2) organic particles such as acrylic or methacrylic, vinyl chloride, vinyl acetate, nylon, styrene / acrylic, styrene / butadiene, polystyrene / acrylic, polystyrene / isoprene, polystyrene / isoprene, methyl methacrylate / butyl methacrylate, melamine, polycarbonate, urea, epoxy, urethane, phenol, diallyl phthalate, and polyester. Of these, silica is particularly preferred in order to provide the coating layer with an appropriate degree of slipperiness.

[0047] The average particle size of the particles is preferably 10 nm or more, more preferably 20 nm or more, and further preferably 30 nm or more. When the average particle size of the particles is 10 nm or more, the particles are less likely to aggregate and lubricity can be ensured, which is preferable.

[0048] The average particle size of the particles is preferably 1000 nm or less, more preferably 800 nm or less, and further preferably 600 nm or less. When the average particle size of the particles is 1000 nm or less, transparency is maintained and the particles do not fall off, which is preferable.

[0049] In addition, for example, it is also preferable to mix small particles having an average particle size of about 10 to 270 nm with large particles having an average particle size of about 300 to 1000 nm, in order to balance slipperiness and smoothness by reducing the average length of the roughness curve element (RSm) while keeping the regional surface average roughness (Sa) and maximum projection height (RP) small, as described below, and it is particularly preferable to use small particles having an average particle size of 30 nm or more and 250 nm or less with large particles having an average particle size of 350 to 600 nm. When mixing small particles and large particles, it is preferable to make the mass content of the small particles larger than the mass content of the large particles with respect to the entire solid content of the coating layer.

[0050] From the viewpoint of reducing pinholes, it is preferable not to use recycled materials for the flat layer on which the release layer is to be formed, in order to prevent the inclusion of particles of lubricants or the like.

[0051] The thickness ratio of the flat layer, which is the layer on the side where the release layer is provided, is preferably 20% to 50% of the total thickness of the base film. If it is 20% or more, the film is less likely to be affected by particles contained in the easy-slip layer B, etc., from the inside, and the area surface average roughness Sa is easily able to satisfy the above range, which is preferable. If it is 50% or less of the total thickness of the base film, the ratio of recycled raw materials used in the easy-slip layer can be increased, which is preferable because it reduces the environmental load.

[0052] From the viewpoint of economic efficiency, the layers other than the flat layer (the easy-slip layer or the above-mentioned core layer) can be made of 50 to 90% by mass of recycled raw materials such as film scraps and PET bottles. Even in this case, it is preferable that the type and amount of the lubricant contained in the easy-slip layer B, the particle size, and the area surface average roughness (Sa) satisfy the above ranges.

[0053] In addition, in order to improve the adhesion of a release layer to be applied later, a coating layer may be provided on the surface of the flat layer before stretching or after uniaxial stretching in the film-forming process, and corona treatment may also be performed. When a coating layer is also provided, the Sa of each layer is substituted with the measured value of the coating layer surface. In addition, when these coating layers are provided on the surface of the flat layer A, it is preferable that they do not contain particles.

[0054] (Antistatic layer) The present invention has an antistatic layer on the surface of the polyester film opposite to the surface having the release layer, The antistatic layer contains an antistatic resin and a wax.

[0055] Furthermore, the average roughness (Sa1) of the release layer described below is smaller than 10 nm, and the average roughness (Ra1) of the release layer and the average roughness (Ra2) of the antistatic layer satisfy the following formula: 0.02 <Sa1 / Sa2<0.5 The antistatic layer contains an antistatic resin and a wax, and furthermore, (Ra1 / Ra2) satisfies a predetermined condition. Therefore, for example, in the process of printing electrodes on a molded ceramic green sheet, when the surface of the release film opposite the processing surface where the ceramic green sheet is provided comes into contact with a support in a dryer and the sheet is transported while undergoing friction, the present invention can suppress static electricity caused by friction.

[0056] The present invention can suppress the charge generation during transport, and therefore can suppress the inclusion of foreign matter due to charge generation caused by friction. Furthermore, the transportability is good, and the occurrence of poor winding and wrinkles in the film that may occur during film transport can be suppressed.

[0057] Furthermore, since the present invention has a good balance between good antistatic properties and winding properties, damage to the green sheet during molding of the thin layer region of the ceramic green sheet can be suppressed, and further, displacement of the printed electrodes can be suppressed.

[0058] In addition, the present invention can suppress not only the generation of charge when the ceramic green sheet is peeled off from the release film, but also the generation of charge during transportation.

[0059] Here, the present invention has excellent adhesion between the substrate and the antistatic layer, and the antistatic layer can be prevented from falling off due to friction between the antistatic layer and the support in the dryer. In addition, the present invention can suppress process contamination caused by the antistatic resin falling off the antistatic layer and the generation of pinholes in the green sheet, and can also solve new problems caused by the falling off of the antistatic resin.

[0060] The antistatic resin constituting the antistatic layer in the release film of the present invention may be a resin having a chargeable or hydrophilic functional group. As the antistatic resin, a vinyl-based resin having a chargeable or hydrophilic functional group is preferable.

[0061] For example, the antistatic resin may be a polymer type of known antistatic agent, such as an anionic antistatic agent of the alkyl sulfate type or alkyl phosphate type, a cationic antistatic agent of the quaternary ammonium salt type, quaternary ammonium resin type or imidazoline type, a nonionic antistatic agent of the sorbitan type or ether type, or a polymer conductive agent such as a composite of poly(3,4-ethylenedioxythiophene) and polystyrenesulfonic acid. The antistatic resin is preferably a resin having a cationic functional group, and particularly preferably an acrylic resin having a cationic functional group.

[0062] By using the organic antistatic agent as described above, even if the conductive organic material falls off or gets mixed into the ceramic green sheets, it disappears during the firing process of the multilayer ceramic capacitor, making it possible to prevent problems caused by residual conductive material.

[0063] Preferably, the antistatic resin is a cationic antistatic agent. For example, the antistatic layer contains a cationic antistatic agent and a wax that is solid under an environmental condition of 25°C, so that the surface resistivity and the surface resistivity after wear can be brought to a predetermined range, and charging due to friction can be suppressed. Furthermore, since charging during transport can be suppressed, the inclusion of foreign matter due to charging caused by friction can be suppressed. Furthermore, transportability is also good, and poor winding of the film and the occurrence of wrinkles that may occur during film transport can be suppressed.

[0064] Furthermore, since the present invention has a good balance between good antistatic properties and winding properties, damage to the green sheet during molding of the thin layer region of the ceramic green sheet can be suppressed, and further, displacement of the printed electrodes can be suppressed.

[0065] In addition, the present invention can not only suppress the generation of charge when the ceramic green sheet is peeled off from the release film, but also suppress the generation of charge during transportation.

[0066] Moreover, the antistatic layer contains a cationic antistatic agent and a wax that is solid under an environmental condition of 25° C., which provides excellent adhesion between the substrate and the antistatic layer, and prevents the antistatic layer from falling off due to friction between the antistatic layer and the support in the dryer. In addition, process contamination caused by the antistatic resin falling off from the antistatic layer and the generation of pinholes in the green sheet can be suppressed, and new problems caused by the falling off of the antistatic resin can also be solved.

[0067] In addition, it is essential to add wax to the antistatic layer in the release film of the present invention as a component that imparts easy slippage. In addition, in the present invention, by including a wax component in the antistatic layer, the surface resistivity after abrasion can be brought into the range described in the present specification.

[0068] This is presumably because the antistatic resin contained in the antistatic layer interacts with the wax, improving the abrasion resistance of the antistatic layer and preventing a sudden increase in the surface resistivity after the abrasion test.

[0069] As the wax, known waxes such as polyester wax and polyolefin wax can be used. For example, polyolefin wax is preferred.

[0070] It is presumed that the inclusion of the polyolefin wax in the antistatic layer improves the abrasion resistance of the antistatic layer due to the interaction between the antistatic resin and the wax, and thus makes it possible to suppress a sudden increase in the surface resistivity value after the abrasion test. The polyolefin wax may contain one or more of a polyethylene wax and a polypropylene wax.

[0071] It is preferable that the wax, particularly the polyolefin wax, is solid under an environmental condition of 25° C. This is because if the wax exists as a liquid at room temperature, there is a possibility that the wax will be significantly transferred to the release layer when the release film is wound into a roll.

[0072] In addition, since the wax is solid under an environmental condition of 25° C., it is possible to prevent the surface shape of the polyester film from being directly transferred to the antistatic layer. Although it is not intended to be limited to a particular theory, it is presumed that, since the wax is solid under an environmental condition of 25° C., the surface shape of the polyester film in the antistatic layer, such as the surface roughness and surface height, is alleviated, leading to the surface shape of the antistatic layer.

[0073] The melting point or softening point of the wax, particularly the polyolefin wax, is not particularly limited, but is preferably 170° C. or lower, and more preferably, for example, 150° C. or lower, or 120° C. or lower. When the wax has a melting point or softening point of 170° C. or lower, it becomes easier to deform when rubbed, and can promote easy slipping.

[0074] In one embodiment, the polyolefin wax has a melting or softening point of 170°C or less, and can be 150°C or less, for example, has a melting or softening point of 120°C or less, and is solid at an ambient condition of 25°C.

[0075] The form of the wax is not particularly limited, but is preferably an aqueous dispersion of the wax in which the wax is dispersed in an aqueous medium, or an aqueous solution of the wax in which the wax is dissolved in an aqueous medium.

[0076] This is because the wax is easily mixed with the electrostatic composition constituting the antistatic layer by being dispersed or dissolved in an aqueous medium. The number average particle size of the wax particles in the aqueous dispersion of the wax is not particularly limited, but is 5 μm or less, for example 0.1 μm or more, from the viewpoints of storage stability and mixing stability.

[0077] In the present invention, the ratio of the mass of the compound having a Si atom to the mass of the wax contained in the antistatic layer is preferably 1 / 50 or less, more preferably 1 / 100 or less. In particular, in the present invention, it is desirable that the antistatic layer contains wax as a lubricant and does not substantially contain a compound having a Si atom, particularly a compound having a siloxane bond. This is to suppress the compound having a siloxane bond from being significantly transferred to the release layer when the release film is wound into a roll.

[0078] In the present invention, "substantially free of compounds having Si atoms" can be defined by the surface Si element ratio of the antistatic layer. Specifically, the Si element ratio (at%) contained in the antistatic layer is less than 1.0 (at%), preferably 0.5 (at%), and may be less than 0.1 (at%), and most preferably a content below the detection limit.

[0079] This is because even if compounds having Si atoms, particularly compounds having siloxane bonds, are not actively added to the film, contaminants from foreign matter or dirt adhering to the raw resin or the lines and equipment during the film manufacturing process may peel off and become mixed into the film.

[0080] The Si element ratio can be measured, for example, by ESCA. An example of the device is K-Alpha+ (manufactured by Thermo Fisher Scientific). Detailed measurement conditions are as follows. For example, a measurement device is used to narrow scan the five elements C, O, N, S, and Si on the surface of the antistatic layer, and the Si element ratio (at %) can be calculated from this using the following formula. (In the present invention, the Si element ratio refers to the ratio (at%) of Si among the five elements C, O, N, S, and Si.) Si element ratio (at%)={Si / (C+O+N+S+Si)}×100...Formula In addition, background was removed by the Shirley method during the analysis, and the surface Si element ratio was calculated as the average value of the measurement results at three or more points.

[0081] Measurement conditions Excitation X-ray: Monochromatic AlKa ray X-ray output: 12kV, 6mA Photoelectron escape angle: 90° Spot size: 400mmf (approx.) Pass energy: 50 eV Step: 0.1eV The wax content in the antistatic layer is 1% by mass to 65% by mass in terms of the total solid content (100% by mass). The wax mixing ratio is, for example, 10% by mass to 60% by mass, or 14% by mass to 56% by mass.

[0082] By setting the wax ratio to 1% by mass or more, sufficient lubricity can be ensured between the release layer and the antistatic layer, or between the antistatic layer and various metal materials or rubber materials such as the transport rolls during the green sheet molding process or the support inside the dryer, etc. Also, deterioration of the antistatic ability due to the falling off of the antistatic layer can be suppressed.

[0083] On the other hand, if the wax ratio is 65 mass% or less, excess wax can be prevented from contaminating the release layer or the transportation process during the green sheet molding process, and the film can be prevented from meandering during transportation or poor winding when wound up due to the film being too slippery.

[0084] In addition to wax for conductive organic substances, binders, crosslinking agents, curing catalysts, etc. may be added to the antistatic layer as long as they do not inhibit antistatic properties and lubricity. Further, when the antistatic layer and the lubricious layer are simultaneously provided by an in-line coating method as described above, particles may be added as a lubricious component.

[0085] The thickness of the antistatic layer is preferably 0.005 to 0.1 μm, particularly preferably 0.01 to 0.05 μm. If the thickness of the antistatic layer is 0.005 μm or less, the function as an antistatic layer cannot be exhibited. On the other hand, when the thickness of the antistatic layer is 0.1 μm or more, peeling of the coating film from the antistatic layer occurs, which is unsuitable.

[0086] The average surface roughness (Sa2) of the surface of the antistatic layer region is 10 nm or more and 40 nm or less, and may be 10 nm or more and 35 nm or less.

[0087] The average roughness (Sa1) of the release layer and the average roughness (Sa2) of the antistatic layer satisfy the following formula: 0.02 < Sa1 / Sa2 < 0.5. Preferably, 0.03 < Sa1 / Sa2 < 0.35, and may be 0.03 < Sa1 / Sa2 < 0.25. For example, 0.035 < Sa1 / Sa2 < 0.25, and 0.035 < Ra1 / Ra2 < 0.150 may also be acceptable.

[0088] By satisfying such conditions, the release surface maintains smoothness, and the opposite surface of the release surface has an appropriate surface roughness, so that lubricity can be ensured for the entire film.

[0089] On the other hand, when Sa1 / Sa2 is 0.02 or less, the opposite surface (antistatic layer) may be too rough with respect to the smoothness of the release surface of the film, and the particles constituting the lubricious surface may easily fall off, or the roughness of the opposite surface may be transferred to the release surface, resulting in the occurrence of pinholes during the production of the ceramic green sheet.

[0090] Furthermore, when Sa1 / Sa2 is 0.5 or more, the slipperiness of the film may be insufficient.

[0091] The surface resistivity value [Rs value] of the antistatic layer is 1.0×10 6 ~1.0×10 12 (Ω / □), preferably 1.5×10 9 ~1.0×10 11 (Ω / □).

[0092] By having the surface resistivity within the above range, when the release film is used for processing, it is possible to suppress the generation of static electricity when the film is wound up and unwound into a roll, and the generation of frictional static electricity when the film comes into contact with the processing machine table.

[0093] In the present invention, regarding the relationship between the surface resistivity, the measurement method of which is described in the Examples, and the surface resistivity after abrasion, the antistatic layer having the configuration of the present invention can reduce the variation in the surface resistivity even after abrasion. That is, the present invention can prevent the antistatic layer from peeling off from the polyester substrate and from being partially scraped off, even after the antistatic layer is abraded.

[0094] By having the above-mentioned relationship between the surface resistivity of the antistatic layer and the surface resistivity after wear, it is possible to prevent the antistatic layer from falling off due to friction between the antistatic layer and the support in the dryer, and it is also possible to suppress process contamination caused by the antistatic resin falling off the antistatic layer and the generation of pinholes in the green sheet, and to solve new problems caused by the falling off of the antistatic resin.

[0095] In the antistatic layer of the present invention, the dynamic friction coefficient (μd) is, for example, more than 0.10 μd and not more than 0.45 μd, may be more than 0.12 μd and not more than 0.40 μd, or may be more than 0.12 μd and not more than 0.35 μd, for example, 0.13 μd or more and not more than 0.26 μd.

[0096] In the present invention, by having the dynamic friction coefficient within the above range and further having Sa1 / Sa2 satisfy a predetermined relationship, it is possible to achieve a good balance between suppression of particle falling off and suppression of unwinding electrification.

[0097] (Release layer) The material constituting the release layer of the release film for molding ceramic green sheets according to this embodiment is not particularly limited as long as it satisfies the flatness required for the release layer. For example, known materials such as silicone compounds, fluorine compounds, alkyd compounds, melamine compounds, and epoxy compounds can be used.

[0098] In one embodiment, the release layer includes polydimethylsiloxane. It may also include at least two kinds of polydimethylsiloxane. For example, it may include a vinyl-modified silicone resin having at least one vinyl group in the structure of polydimethylsiloxane as the first polydimethylsiloxane, and a polymethylhydrogensiloxane having at least one hydrosilyl group in the structure of polydimethylsiloxane as the second polydimethylsiloxane.

[0099] By including polydimethylsiloxane in the release layer and having the antistatic layer of the present invention, the difference in surface free energy between the release layer and the antistatic layer is reduced, which makes it possible to prevent the wax in the antistatic layer from migrating to the release layer, and to maintain the abrasion resistance of the antistatic layer even after long-term storage.

[0100] The thickness of the release layer in the present invention is preferably 0.001 to 0.2 μm, more preferably 0.005 to 0.1 μm, as the thickness after drying. If it is 0.001 μm or more, a release layer with excellent releasability can be obtained, which is preferable. If it is 0.2 μm or less, it is not necessary to increase the solid content concentration of the release layer components or the coating amount, and it is preferable that the coating property is excellent when applied onto the substrate film.

[0101] In the present invention, the method for forming the release layer is not particularly limited, and a method is used in which a coating liquid in which a releasing compound is dissolved or dispersed is spread on one side of the polyester film of the substrate by coating or the like, and the solvent is removed by drying, followed by curing. The release layer may also be provided simultaneously with the formation of the polyester film by an in-line coating method.

[0102] The area surface average roughness (Sa1) of the release layer is 0.1 nm or more and 10 nm or less, for example, 0.3 nm or more and 8 nm or less. For example, the area surface average roughness (Sa1) of the release layer is within the range of the surface average roughness (Sa1) of the release layer side surface of the substrate ±2 nm, may be in the range of ±1.5 nm, may be in the range of ±1.2 nm. By including the first and second polydimethylsiloxanes according to the present invention, the release layer exhibits high smoothness and excellent ceramic peeling force, and further, the surface free energy difference between the release layer and the antistatic layer can be reduced.

[0103] (Release film for ceramic green sheet molding) The release film for molding a ceramic green sheet of the present invention has a release layer on one side of a polyester film, and has an antistatic layer on the side opposite to the side having the release layer on one side of the polyester film.

[0104] In the present invention, the release layer and the antistatic layer are provided separately on both sides of the polyester film, and the average roughness (Sa1) of the release layer is small and the average roughness (Sa2) of the antistatic layer is larger than that of the release layer. 0.02 <Sa1 / Sa2<0.5 By satisfying the above relationship, the antistatic layer does not impair the releasability or flatness of the release layer, and since the antistatic layer is exposed, it is possible to suppress unwinding static electricity during film transport.

[0105] In addition, the above-mentioned structure can also prevent the generation of static electricity during peeling of the ceramic green sheet. Although the mechanism behind this is unclear, it is believed that the static electricity generated during peeling is quickly transferred to the antistatic layer on the back side.

[0106] On the other hand, by adding a wax component to the antistatic layer, it is possible to overcome problems such as a release layer with a large average roughness damaging the release layer and the convex parts of the antistatic layer being scraped off during film transport.

[0107] The order in which the release layer and the antistatic layer are provided on the film is not particularly limited. The release layer may be provided first and then the antistatic layer, or the release layer may be provided after the antistatic layer is provided together with the lubricating coating layer by in-line coating. Moreover, the release layer and the antistatic layer may be provided simultaneously regardless of in-line coating or off-line coating.

[0108] (Second embodiment) In another embodiment, the present invention provides a release film for molding a ceramic green sheet, as described below.

[0109] A polyester film as a substrate; A polyester film having a release layer on one side, The polyester film has an antistatic layer on the surface opposite to the surface having the release layer. A release film for molding a ceramic green sheet, The substrate has two surfaces with different roughnesses, the polyester film contains particles on the release layer side and the antistatic layer side, the antistatic layer contains an antistatic resin and a wax, The average surface roughness (Sa1) of the release layer is 3 nm or more and less than 10 nm, and The area surface average roughness (Sa1) of the release layer and the area surface average roughness (Sa2) of the antistatic layer satisfy the following formula: Release film for ceramic green sheet molding; 0.02 <Sa1 / Sa2<0.5。

[0110] In this embodiment, the polyester film as the substrate contains particles at least on the release layer side and the antistatic layer side, and preferably the area average surface roughness on the release layer side is smaller than the area average surface roughness on the antistatic layer side.

[0111] The area on the mold layer side has an average surface roughness of 3 nm to 10 nm, for example, 3 nm to 8 nm, whereas the area on the antistatic layer side has an average surface roughness of 5 nm to 25 nm, for example, 5 nm to 20 nm.

[0112] Furthermore, the average surface roughness (Sa1) of the release layer and the average surface roughness (Sa2) of the antistatic layer satisfy the following formula: 0.02 <Sa1 / Sa2<0.5。

[0113] Such a release film can suppress static electricity caused by friction, for example, in a process of printing electrodes on a molded ceramic green sheet, when the surface of the release film opposite the processing surface on which the ceramic green sheet is to be applied comes into contact with a support inside a dryer and the sheet is transported while undergoing friction.

[0114] The present invention can suppress the charge generation during transport, and therefore can suppress the inclusion of foreign matter due to charge generation caused by friction. Furthermore, the transportability is good, and the occurrence of poor winding and wrinkles in the film that may occur during film transport can be suppressed.

[0115] Furthermore, since the present invention has a good balance between good antistatic properties and winding properties, damage to the green sheet during molding of the thin layer region of the ceramic green sheet can be suppressed, and further, displacement of the printed electrodes can be suppressed.

[0116] In addition, the present invention can suppress not only the generation of charge when the ceramic green sheet is peeled off from the release film, but also the generation of charge during transportation.

[0117] Here, the present invention has excellent adhesion between the substrate and the antistatic layer, and the antistatic layer can be prevented from falling off due to friction between the antistatic layer and the support in the dryer. In addition, the present invention can suppress process contamination caused by the antistatic resin falling off the antistatic layer and the generation of pinholes in the green sheet, and can also solve new problems caused by the falling off of the antistatic resin.

[0118] Conditions other than the average surface roughness of the substrate, such as the composition of the substrate, the release layer, the antistatic layer, and other conditions constituting the present invention, may be the same as those described in this specification.

[0119] Also, in this embodiment, 0.1 <Sa1 / Sa2<0.5であってもよく、0.2<Sa1 / Sa2<0.5であってもよい。

[0120] In another aspect, the present invention provides a method for producing a release film for molding a ceramic green sheet.

[0121] In one embodiment, the method of the present invention includes applying a release layer-forming coating liquid to a polyester film as a substrate. In this step, the release layer-forming coating liquid is applied to the surface of the polyester film having a release layer, and the surface does not substantially contain particles.

[0122] Preferably, the substrate coated with the release layer-forming coating liquid is carried into the first drying furnace within a time period of 0.1 to 10 seconds after coating of the coating liquid, and particularly preferably within a time period of 0.1 to 5 seconds. The drying temperature in the first drying oven may be 70°C or more and 110°C or less, or 80°C or more and 100°C or less. Furthermore, the laminated film obtained may be carried into a second drying oven following the first drying oven. The drying temperature in the second drying oven may be 80°C or more and 130°C or less. Preferably, the drying temperature in the first drying oven is set lower than the drying temperature in the second drying oven. In addition to the first and second drying ovens, an additional drying oven may be provided.

[0123] The resulting laminated film is then irradiated with ultraviolet light on a cooling roll to form a release layer. The release layer obtained through such a process can satisfy the various physical properties and effects described in this specification.

[0124] Although not limited to a specific theory, it is believed that in the manufacturing method of the present invention, the transport time to the first drying oven, the drying temperature in the first drying oven, and the drying temperature in the second drying oven are controlled to the above conditions, so that the first polydimethylsiloxane and the second polydimethylsiloxane contained in the release layer can be well dispersed. As a result, the difference in surface free energy between the release layer and the antistatic layer can be reduced, the wax in the antistatic layer can be prevented from migrating to the release layer, and the wear resistance of the antistatic layer can be maintained even after long-term storage.

[0125] The production method of the present invention further includes a step of forming an antistatic layer on the surface of the obtained release-coated film opposite to the release layer, for example, by providing a lubricating layer on a polyester film as a substrate and applying an antistatic layer-forming coating liquid to the lubricating layer.

[0126] Preferably, the laminated film coated with the antistatic layer-forming coating liquid is carried into the first drying oven 0.1 to 10 seconds after the coating liquid is applied. Particularly preferably, the time is 0.1 to 5 seconds. The drying temperature in the first drying oven may be 70°C to 110°C, or 80°C to 100°C. Furthermore, the laminated film obtained may be carried into a second drying oven following the first drying oven. The drying temperature in the second drying oven may be 80°C to 130°C. Preferably, the drying temperature in the first drying oven is set lower than the drying temperature in the second drying oven. In addition to the first and second drying ovens, an additional drying oven may be provided.

[0127] In this specification, the first drying oven and the second drying oven may be the same drying oven, or a first drying oven and a second drying oven may be provided separately for the step of forming the release layer and the step of forming the antistatic layer, respectively. In either step, it is sufficient that the above-mentioned drying conditions are applicable.

[0128] The antistatic layer obtained through such processes can satisfy the various physical properties and effects described in this specification, and further, a release film for molding ceramic green sheets can be obtained that satisfies the various physical properties and effects described in this specification.

[0129] Although not intended to be limited to any particular theory, in the production method of the present invention, by controlling the transport time to the first drying oven, the drying temperature in the first drying oven, and the drying temperature in the second drying oven to the above-mentioned conditions, the synergistic effect of the antistatic resin and wax contained in the antistatic layer results in the regional average surface roughness (Sa2) of the antistatic layer without the surface shape of the polyester film being directly transferred to the antistatic layer.

[0130] For this reason, (Sa1 / Sa2) according to the present invention falls within a predetermined range, and the release film obtained by the manufacturing method of the present invention can, for example, have a good balance of good antistatic properties and winding properties, can suppress damage to the green sheet during molding of the ceramic green sheet in the thin layer region, and can also suppress misalignment of the printed electrodes.

[0131] In addition, the difference in surface free energy between the release layer and the antistatic layer can be reduced, and the wax in the antistatic layer can be prevented from migrating to the release layer, making it possible to maintain the abrasion resistance of the antistatic layer even after long-term storage.

[0132] The release film of the present invention is produced, for example, through the above-mentioned steps.

[0133] (Ceramic green sheet) The ceramic green sheet in the present invention is not particularly limited as long as it is a sheet containing a resin. In one embodiment, the release film of the present invention is a release film for molding a ceramic green sheet containing an inorganic compound. Examples of inorganic compounds include metal particles, metal oxides, minerals, and the like, and examples thereof include calcium carbonate, silica particles, aluminum particles, and barium titanate particles. Since the present invention has a release layer with high smoothness, even in an embodiment in which the ceramic green sheet contains these inorganic compounds, defects that may be caused by inorganic compounds, such as breakage of the ceramic green sheet and difficulty in peeling the ceramic green sheet from the release layer, can be suppressed.

[0134] The resin component forming the ceramic green sheet can be appropriately selected depending on the application. In one embodiment, the ceramic green sheet containing an inorganic compound is a ceramic green sheet. For example, the ceramic green sheet can contain barium titanate as an inorganic compound. Also, the resin component can contain, for example, a polyvinyl butyral resin.

[0135] In one embodiment, the ceramic green sheet has a thickness of 0.2 μm or more and 1.0 μm or less. For example, the present invention can provide a method for producing a release film for producing a ceramic green sheet containing such an inorganic compound. In addition, the method for producing a release film for molding a ceramic green sheet in the present invention may include a step of molding a ceramic green sheet having a thickness of 0.2 μm or more and 1.0 μm or less.

[0136] In addition, the laminated polyester film constituting the release film of the present invention has a planar layer that does not substantially contain inorganic particles on the release layer side, and a lubricating layer that can contain particles on the antistatic layer side. In the present invention, the antistatic layer has wax, which makes it possible to prevent the particles of the lubricating layer from falling off. Moreover, compared with conventional release films, the particles can be prevented from falling off even more effectively.

[0137] This is because the presence of wax can suppress the force acting on the particles when the conveying roll and the lubricious layer rub against each other strongly during the manufacture of the multilayer ceramic capacitor.

[0138] Furthermore, the release film of the present invention can significantly suppress charging when the film is unwound. By significantly suppressing charging when the film is unwound, it is possible to suppress adhesion of foreign matter caused by charging of the film in the ceramic green sheet production process and process defects caused by the occurrence of sparks, etc., and as a result, it is possible to produce a multilayer ceramic capacitor of higher quality.

[0139] (Ceramic green sheets and multilayer ceramic capacitors) Generally, a multilayer ceramic capacitor has a rectangular parallelepiped ceramic body. Inside the ceramic body, first internal electrodes and second internal electrodes are alternately provided along the thickness direction. The first internal electrodes are exposed on a first end face of the ceramic body. A first external electrode is provided on the first end face. The first internal electrode is electrically connected to the first external electrode at the first end face. The second internal electrode is exposed on a second end face of the ceramic body. A second external electrode is provided on the second end face. The second internal electrode is electrically connected to the second external electrode at the second end face.

[0140] In one embodiment, the release film of the present invention is a release film for producing a ceramic green sheet, and is used to produce such a multilayer ceramic capacitor. For example, the method for producing a ceramic green sheet by using the release film for producing a ceramic green sheet of the present invention to form a ceramic green sheet can form a ceramic green sheet having a thickness of 0.2 μm or more and 1.0 μm or less. More specifically, for example, the ceramic green sheet is manufactured as follows. First, the release film of the present invention is used as a carrier film, and a ceramic slurry for forming a ceramic body is applied and dried. The ceramic green sheet is required to have a thickness of 0.2 to 1.0 μm. A conductive layer for forming a first or second internal electrode is printed on the applied and dried ceramic green sheet. A mother laminate is obtained by appropriately stacking and pressing a ceramic green sheet, a ceramic green sheet on which a conductive layer for forming a first internal electrode is printed, and a ceramic green sheet on which a conductive layer for forming a second internal electrode is printed. The mother laminate is divided into a plurality of pieces to prepare a raw ceramic body. The raw ceramic body is fired to obtain a ceramic body. Then, a first and second external electrodes are formed to complete a multilayer ceramic capacitor. EXAMPLES

[0141] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The property values ​​used in the present invention were evaluated using the following methods.

[0142] (area surface roughness Sa) Measurements were performed under the following conditions using a non-contact surface shape measurement system (VertScan R550H-M100). The area surface average roughness (Sa) was calculated by averaging five measurements.

[0143] (Measurement conditions) Measurement mode: WAVE mode Objective lens: 50x 0.5×Tube lens ·Measurement area: 187μm×139μm (Analysis conditions) Surface correction: 4th order correction -Interpolation process: Fully interpolated

[0144] (Ceramic green sheet peeling force) Slurry composition I consisting of the following materials was mixed by stirring for 10 minutes, and dispersed with zirconia beads having a diameter of 0.5 mm using a bead mill for 10 minutes to obtain a primary dispersion. Slurry composition II consisting of the following materials was then added to the primary dispersion so that the ratio of (slurry composition I):(slurry composition II) was 3.4:1.0, and secondary dispersion was performed with zirconia beads having a diameter of 0.5 mm using a bead mill for 10 minutes to obtain a ceramic slurry.

[0145] (Slurry Composition I) Toluene 22.3 parts by mass Ethanol 18.3 parts by mass Barium titanate (average particle size 100 nm) 57.5 parts by mass Homogenol L-18 (Kao Corporation) 1.9 parts by weight (Slurry Composition II) Toluene 39.6 parts by mass Ethanol 39.6 parts by mass Dioctyl phthalate 3.3 parts by mass Polyvinyl butyral (S-LEC BM-S, manufactured by Sekisui Chemical Co., Ltd.) 16.3 parts by weight 1-Ethyl-3-methylimidazolium ethyl sulfate 0.5 parts by mass Next, the release surface of the obtained release film sample was coated with an applicator so that the slurry after drying would be 1.0 μm, and dried at 60 ° C for 1 minute to obtain a release film with a ceramic green sheet. The obtained release film with a ceramic green sheet was de-electrified using a static eliminator (Keyence Corporation, SJ-F020), and then peeled off using a peel tester (Kyowa Interface Science Co., Ltd., VPA-3, load cell load 0.1 N) at a peel angle of 90 degrees, a peel temperature of 25 ° C, and a peel speed of 10 m / min. For the peeling direction, a double-sided adhesive tape (Nitto Denko Corporation, No. 535A) was attached to a SUS plate attached to the peel tester, the ceramic green sheet side was attached to the double-sided tape, and the release film was fixed on it, and the release film side was pulled to peel it off.

[0146] (Pinhole evaluation of ceramic green sheets) A ceramic green sheet having a thickness of 1 μm was molded on the release surface of the release film in the same manner as in the evaluation of the releasability of the ceramic slurry. The release film was then peeled off from the molded ceramic green sheet-attached release film to obtain a ceramic green sheet. Light was applied to the opposite side of the ceramic slurry coating surface in a range of 25 cm2 in the central region in the film width direction of the obtained ceramic green sheet, and the occurrence of pinholes through which light was transmitted was observed and visually evaluated according to the following criteria. ○: No pinholes ×: One or more pinholes

[0147] (Slipperiness of antistatic layer) The static friction coefficient (μs) and dynamic friction coefficient (μd) of the contact surface were measured using a Tensilon universal testing machine (A&D Corporation, RTG-1210) under the following conditions in accordance with JIS K-7125 when the antistatic layer surface of the film was placed in contact with a stainless steel plate. Test piece: width 50mm x length 60mm Load capacity: 4.4kg Test speed: 200mm / min Friction material: SUS plate

[0148] (Surface resistance value of antistatic layer) After leaving the film in an atmosphere of 23°C and 65% RH for 24 hours, the surface resistivity (Ω / □) of the film surface, i.e., the antistatic layer, was measured in that atmosphere using a surface resistance measuring device (Hiresta-IP, manufactured by Mitsubishi Petrochemical Co., Ltd.) at an applied voltage of 500 V.

[0149] (Surface resistance value of antistatic layer after abrasion test) The film was rubbed with the load head of a Gakushin friction tester (Yamaguchi Kagaku Sangyo Co., Ltd.) using pearl paper (Toyobo Ester Film P4255-35, Toyobo Co., Ltd.) with gauze (Hakujuji Gauze, Hakujuji Co., Ltd.) at the contact point between the load head and the film, with a load of 200gf / 25mm2 (5mm x 5mm) [0.0785MPa]. The antistatic layer of the film was rubbed back and forth with the load head 10 times, and then left for 24 hours in an atmosphere of 23°C and 65% RH. The rubbed area was then measured for the surface resistivity (Ω / □) of the film surface, i.e., the antistatic layer, using a surface resistance measurement device (Hiresta-IP, Mitsubishi Petrochemical Co., Ltd.) at an applied voltage of 500V.

[0150] (Particle shedding) A film (3 cm (film width direction) x 20 cm (film length direction)) was attached to a friction fastness tester (Daiei Scientific Instruments Manufacturing Co., Ltd., RT-200) with the antistatic layer facing up, and aluminum foil (thickness 80 μm, arithmetic average surface roughness 0.03 μm) was used as the contact point between the load head (2 cm x 2 cm, 200 g) and the sample film, and the film was moved back and forth 10 times over a distance of 10 cm at a speed of 2 seconds per round trip. The obtained film was placed on a black mount and visually confirmed to see if any powder had fallen off. ○: No powder fall was observed on the black backing. △: Slight powder fall was observed overall on the black backing. ×: Powder fall was observed overall on the black backing paper.

[0151] (Charging of release film roll when unwinding) The release film for green sheet production obtained in each Example and Comparative Example was wound up into a roll with a width of 400 mm and a length of 5000 m to obtain a release film roll. After storing this release film roll for 30 days under an environment of 40°C and humidity of 50% or less, the charge amount when rewinding at 100 m / min was measured using "KSD-0103" manufactured by Kasuga Electric Co., Ltd. The charge amount was measured at a point 100 mm away immediately after unwinding and every 500 m of the unwinding length, and the average value was calculated. ○: Less than ±5kV △: ±5kV or more, less than 10kV ×: ±10kV or more

[0152] (Preparation of Polyethylene Terephthalate Pellets (PET(I))) The esterification reaction apparatus used was a continuous esterification reaction apparatus consisting of a three-stage complete mixing tank equipped with an agitator, a partial condenser, a raw material inlet, and a product outlet. The amount of TPA (terephthalic acid) was 2 tons / hour, the amount of EG (ethylene glycol) was 2 moles per mole of TPA, and the amount of antimony trioxide was such that the Sb atom was 160 ppm in the produced PET. The slurry of these was continuously fed to the first esterification reactor of the esterification reaction apparatus and reacted at normal pressure for an average residence time of 4 hours at 255°C. Next, the reaction product in the first esterification reactor was continuously removed from the system and fed to a second esterification reactor, and EG distilled off from the first esterification reactor was fed into the second esterification reactor in an amount of 8 mass% based on the produced PET. Further, an EG solution containing magnesium acetate tetrahydrate in an amount such that the Mg atom would be 65 ppm based on the produced PET, and an EG solution containing TMPA (trimethyl phosphate) in an amount such that the P atom would be 40 ppm based on the produced PET were added, and the reaction was carried out at normal pressure for an average residence time of 1 hour at 260°C. Next, the reaction product in the second esterification reactor was continuously removed from the system and fed to a third esterification reactor, and the reaction was carried out at 39 MPa (400 kg / cm) using a high-pressure disperser (manufactured by Nippon Seiki Co., Ltd.). 2 0.2% by mass of porous colloidal silica with an average particle size of 0.9 μm, which had been subjected to dispersion treatment at a pressure of 1000 g / cm2 and an average number of treatments of 5 passes, and 0.4% by mass of synthetic calcium carbonate with an average particle size of 0.6 μm, to which 1% by mass of ammonium salt of polyacrylic acid was attached per calcium carbonate, were added as 10% EG slurry, and reacted at normal pressure for an average residence time of 0.5 hours at 260°C. The esterification reaction product produced in the third esterification reactor was continuously fed to a three-stage continuous polycondensation reactor to carry out polycondensation, filtered through a filter made of sintered stainless steel fibers with a 95% cut diameter of 20 μm, then ultrafiltered and extruded into water, cooled, and cut into chips to obtain PET chips with an intrinsic viscosity of 0.60 dl / g (hereinafter abbreviated as PET(I)). The lubricant content in the PET chips was 0.6% by mass.

[0153] (Preparation of polyethylene terephthalate pellets (PET(II))) On the other hand, in the production of the PET(I) chips, PET chips containing absolutely no particles such as calcium carbonate or silica and having an intrinsic viscosity of 0.62 dl / g were obtained (hereinafter, abbreviated as PET(II)).

[0154] (Manufacture of laminated film F1) After drying, these PET chips were melted at 285°C, melted at 290°C using a separate melt extruder, and filtered in two stages using a filter made of sintered stainless steel fibers with a 95% cut diameter of 15μm and a filter made of sintered stainless steel particles with a 95% cut diameter of 15μm. The mixture was joined in a feed block, and PET (I) was laminated as an easy-slip layer (layer opposite to the release surface side) and PET (II) was laminated as a flat layer (layer on the release surface side). The mixture was extruded (casted) at a speed of 45m / min into a sheet, and electrostatically adhered and cooled on a casting drum at 30°C by an electrostatic adhesion method to obtain an unstretched polyethylene terephthalate sheet with an intrinsic viscosity of 0.59dl / g. The layer ratio was adjusted so that PET (I) / (II) = 60% by mass / 40% by calculation of the discharge amount of each extruder. Next, this unstretched sheet was heated with an infrared heater, and then stretched 3.5 times in the longitudinal direction by the speed difference between the rolls at a roll temperature of 80°C. The film was then introduced into a tenter and stretched 4.2 times in the transverse direction at 140°C. It was then heat-treated at 210°C in a heat-fixing zone. It was then relaxed 2.3% in the transverse direction at 170°C to obtain a biaxially stretched polyethylene terephthalate film F1 with a thickness of 31 μm. The flat layer A of the obtained film F1 had an Sa of 1 nm, and the easy-slip layer B had an Sa of 28 nm.

[0155] (Manufacture of laminated film F2) The laminated film F2 was laminated in the same manner as the laminated film F1, using PET (II) on both the flat layer side and the easy-slip layer side, extruded (casted) into a sheet at a speed of 45 m / min, electrostatically adhered and cooled on a casting drum at 30°C by the electrostatic adhesion method, and an unstretched polyethylene terephthalate sheet with an intrinsic viscosity of 0.59 dl / g was obtained. This unstretched PET sheet was heated to 100°C by a heated roll group and an infrared heater, and then stretched 3.5 times in the longitudinal direction by a roll group with a difference in peripheral speed to obtain a uniaxially stretched PET film. Next, the following easy-slip coating liquid was applied to one side of the PET film with a bar coater, and then dried at 80°C for 15 seconds. The coating amount was adjusted to 0.1 μm after final stretching and drying. The film was then stretched 4.0 times in the width direction at 150°C in a tenter, heated at 230°C for 0.5 seconds while the length of the film in the width direction was fixed, and then subjected to a 3% width direction relaxation treatment at 230°C for 10 seconds to obtain an in-line coated polyester film F2 having a thickness of 31 μm. The flat layer A of the obtained film F2 had an Sa of 1 nm, and the easy-slip layer B had an Sa of 6 nm.

[0156] (Slip-resistant coating liquid) Water 45.82 parts by mass Isopropyl alcohol 35.00 parts by weight Acrylic polyol resin 10.36 parts by mass (DSM Coating Resins NeoCryl A-614, Tg 74°C, acid value 55%, solid content 32% by mass) Oxazoline-based crosslinking agent D-1 5.68 parts by mass (Solid content concentration 25% by mass) Acrylic particle water dispersion 2.37 parts by weight (Nippon Shokubai, product name MX200W, average particle size 350nm, solid concentration 10% by mass) Acrylic particle water dispersion 0.47 parts by weight (Nippon Shokubai, product name MX300W, average particle size 450nm, solid content concentration 10% by mass) Surfactant H-1 (fluorine-based, solids concentration 10% by mass) 0.30 parts by mass

[0157] (Manufacturing of laminated film F3) As the laminated film F3, E5101 (Toyobo Ester (registered trademark) film, manufactured by Toyobo Co., Ltd.) having a thickness of 25 μm was used. The laminated film F3 was configured so that particles were contained in the flat layer and the easy-slip layer. The Sa of the flat layer A of the laminated film F3 was 12 nm, and the Sa of the easy-slip layer B was 12 nm.

[0158] (Manufacturing of laminated film F4) A 38 μm thick A4000 (Toyobo Ester (registered trademark) film, manufactured by Toyobo Co., Ltd.) was used as the laminated film F4. A4000 does not contain particles in the film. The Sa of the flat layer A of the laminated film F4 was 2 nm, and the Sa of the easy-slip layer B was 2 nm.

[0159] (Manufacture of laminated film F5) The laminated film F5 was X3 (Toyobo Ester (registered trademark) film, manufactured by Toyobo Co., Ltd.) with a thickness of 31 μm. The laminated film F5 was configured to contain particles in the flat layer and the easy-slip layer. The Sa of the flat layer A of the laminated film F5 was 6 nm, and the Sa of the easy-slip layer B was 15 nm.

[0160] (Manufacture of laminated film F6) The laminated film F6 was a 38 μm thick A4000 (Toyobo Ester (registered trademark) film, manufactured by Toyobo Co., Ltd.) film with one side subjected to sand mat processing. The side of the film subjected to sand mat processing was the easy-slip surface, and the opposite side was the flat layer. The Sa of the flat layer A of the laminated film F6 was 3 nm, and the Sa of the easy-slip layer B was 200 nm.

[0161] Example 1 A release layer forming material R1 was prepared by adjusting the ratio of vinyl groups to hydrosilyl groups to 2.0 using a vinyl-modified silicone resin (weight average molecular weight: 466,000) having at least one vinyl group in the polydimethylsiloxane structure as the first polydimethylsiloxane and a polymethylhydrogensiloxane having at least one hydrosilyl group in the polydimethylsiloxane structure as the second polydimethylsiloxane, and the release layer forming coating liquid M1 described below containing the release layer forming material R1 was prepared.

[0162] (Release layer forming coating liquid M1) Methyl ethyl ketone 64.3 parts by mass Toluene 34.0 parts by mass Release layer forming material R1 1.5 parts by weight Adhesion imparting agent 0.1 parts by mass (SD7200 manufactured by Dow Toray Industries, Inc. (reaction product of vinyltriacetoxysilane and glycidoxypropyltrimethoxysilane, solid concentration 90% by mass) Catalyst 0.1 part by mass (SRX212 (Platinum complex of 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, solids concentration 5% by mass, manufactured by Dow Toray Co., Ltd.) A release layer forming coating solution M1 having the following composition was applied onto the flat layer A of the laminated film F1 using reverse gravure so that the coating thickness after drying would be 20 nm. After that, the processing speed was adjusted so that the film entered the first drying oven 0.5 seconds later, and the film was continuously heated and dried at a first drying oven temperature of 90°C and a second drying oven temperature of 120°C. After the drying process, the film was irradiated on a cooling roll with an ultraviolet irradiator (Heraeus, H bulb) with an integrated light dose of 100 mJ / cm2. 2 The release layer was cured by irradiating it with ultraviolet light of 1000 nm.

[0163] On the obtained easy-slip layer B of the release-coated film, the antistatic layer-forming coating solution R1 having the following composition was applied by reverse gravure so that the coating thickness after drying would be 15 nm. After that, the processing speed was adjusted so that the film entered the first drying oven 0.5 seconds later, and the film was continuously heated and dried at a first drying oven temperature of 90°C and a second drying oven temperature of 120°C to obtain a release film for molding ceramic green sheets.

[0164] (Antistatic layer forming coating liquid R1) Water 34.6 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Soken Chemical Industries, Ltd., Elecondo PQ-10, solid content concentration 50% by mass) 0.4 parts by mass Polyethylene wax (Toho Chemical Industry Co., Ltd., Hi-Tec E68A, solid content concentration 20% by mass) 0.6 parts by mass The softening point of the polyethylene wax used in the examples was 110° C. Furthermore, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, good results were obtained as shown in Table 2A.

[0165] Example 2 A release layer forming coating solution M1 having the following composition was applied onto the flat layer A of the laminated film F2 using reverse gravure so that the coating thickness after drying would be 20 nm. After that, the processing speed was adjusted so that the film entered the first drying oven 0.5 seconds later, and the film was continuously heated and dried at a first drying oven temperature of 90°C and a second drying oven temperature of 120°C. After the drying process, the film was irradiated on a cooling roll using an ultraviolet irradiator (Heraeus, H bulb) with an integrated light dose of 100 mJ / cm2. 2 The release layer was cured by irradiating it with ultraviolet light of 1000 nm.

[0166] A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R1 was applied onto the lubrication layer B of the obtained release coated film by reverse gravure so that the coating amount after drying was 15 nm. As a result of evaluating the above-mentioned various physical properties of the obtained release film, good results were obtained as shown in Table 2A.

[0167] Example 3 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R2 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0168] (Antistatic layer forming coating solution R2) Water 34.8 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.5 parts by mass Polyethylene wax (Hitec E68A, manufactured by Toho Chemical Industry Co., Ltd.) 0.3 parts by weight Moreover, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, good results were obtained as shown in Table 2A.

[0169] Example 4 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer forming coating solution R3 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0170] (Antistatic layer forming coating solution R3) Water 34.4 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.3 parts by mass Polyethylene wax (Hitec E68A, manufactured by Toho Chemical Industry Co., Ltd.) 0.9 parts by weight Moreover, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, good results were obtained as shown in Table 2A.

[0171] Example 5 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R4 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0172] (Antistatic layer forming coating solution R4) Water 35.1 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.2 parts by mass Polyethylene wax (Hitec E68A, manufactured by Toho Chemical Industry Co., Ltd.) 0.3 parts by weight Moreover, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, good results were obtained as shown in Table 2A.

[0173] Example 6 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer forming coating solution R5 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 23 nm.

[0174] (Antistatic layer forming coating solution R5) Water 34.1 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.6 parts by mass Polyethylene wax (Hitec E68A, manufactured by Toho Chemical Industry Co., Ltd.) 0.9 parts by weight Moreover, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, good results were obtained as shown in Table 2A.

[0175] Example 7 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R6 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0176] (Antistatic layer forming coating liquid R6) Water 35.1 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.4 parts by mass Polyethylene wax (Hitec E68A, manufactured by Toho Chemical Industry Co., Ltd.) 0.1 parts by weight Moreover, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, a film with sufficient slipperiness was obtained, as shown in Table 2A.

[0177] Example 8 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R7 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0178] (Antistatic layer forming coating solution R7) Water 34.1 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.3 parts by mass Polyethylene wax (Hitec E68A, manufactured by Toho Chemical Industry Co., Ltd.) 1.2 parts by weight Furthermore, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, a film with slightly high slipperiness was obtained, as shown in Table 2A.

[0179] Example 9 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R8 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0180] (Antistatic layer forming coating solution R8) Water 34.8 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.4 parts by mass Polyethylene wax (AQUACER 531, manufactured by BYK Corporation) 0.4 parts by weight The softening point of the polyethylene wax used in the examples was 130° C. Furthermore, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, a film with sufficient particle shedding properties was obtained, as shown in Table 2A.

[0181] Example 10 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that an antistatic layer-forming coating solution R9 having the following composition was applied onto the lubrication layer of the release coating film using a reverse gravure coating so that the coating thickness after drying was 15 nm.

[0182] (Antistatic layer forming coating solution R9) Water 34.8 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.4 parts by mass Polypropylene wax (AQUACER 593, manufactured by BYK Corporation) 0.4 parts by weight The softening point of the polyethylene wax used in the examples was 160° C. Furthermore, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, a film with sufficient particle shedding properties was obtained, as shown in Table 2A.

[0183] (Production Example 11) A release layer forming coating solution M1 having the following composition was applied to one side of the laminated film F5 using reverse gravure so that the coating thickness after drying would be 20 nm. After that, the processing speed was adjusted so that the film entered the first drying oven 0.5 seconds later, and the film was continuously heated and dried at a first drying oven temperature of 90°C and a second drying oven temperature of 120°C. After the drying process, the film was irradiated on a cooling roll with an ultraviolet irradiator (Heraeus, H bulb) with an integrated light dose of 100 mJ / cm2. 2 The release layer was cured by irradiating it with ultraviolet light of 1000 nm.

[0184] A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R1 was applied to the other surface of the obtained release coated film by reverse gravure so that the coating amount after drying was 15 nm. Furthermore, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, good results were obtained as shown in Table 2A.

[0185] Example 12 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R13 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0186] (Antistatic layer forming coating solution R13) Water 33.3 parts by mass Methanol 64.4 parts by mass Anionic antistatic resin (EL Polymer WS-52R, manufactured by Shin-Nakamura Chemical Co., Ltd.) 2 parts by weight Polyethylene wax (Hitec E68A, manufactured by Toho Chemical Industry Co., Ltd.) 0.3 parts by weight Fluorosurfactant (MEGAFAC F-444, manufactured by DIC Corporation) 0.03 parts by weight Furthermore, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, as shown in Table 2A, the surface resistance value was slightly high.

[0187] (Example 13) A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R14 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0188] (Antistatic layer forming coating solution R14) Water 34.6 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Soken Chemical Industries, Ltd., Elecondo PQ-10, solid content concentration 50% by mass) 0.4 parts by mass Polyethylene wax (Toho Chemical Industry Co., Ltd., Hi-Tec E68A, solid content concentration 20% by mass) 0.01 parts by mass The above-mentioned various physical properties of the obtained release film were evaluated, and as a result, a film with slightly high slipperiness was obtained, as shown in Table 2A.

[0189] Example 14 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R15 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0190] (Antistatic layer forming coating solution R15) Water 35.1 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Takemoto Oil Co., Ltd. TIE-615A) 0.2 parts by mass Polyethylene wax (Hitec E68A, manufactured by Toho Chemical Industry Co., Ltd.) 0.3 parts by weight Moreover, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, good results were obtained as shown in Table 2A.

[0191] Comparative Example 1 A release layer forming coating solution M1 having the following composition was applied to one side of the laminated film F3 using reverse gravure so that the coating thickness after drying would be 20 nm. After that, the processing speed was adjusted so that the film entered the first drying oven 0.5 seconds later, and the film was continuously heated and dried at a first drying oven temperature of 90°C and a second drying oven temperature of 120°C. After the drying process, the film was irradiated on a cooling roll with an ultraviolet irradiator (Heraeus, H bulb) with an integrated light dose of 100 mJ / cm2. 2 The release layer was cured by irradiating it with ultraviolet light of 1000 nm.

[0192] A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R1 was applied to the other surface of the obtained release coated film by reverse gravure so that the coating thickness after drying was 15 nm. As a result of evaluating the above-mentioned various physical properties of the obtained release film, many pinholes were generated in the ceramic green sheet as shown in Table 2B.

[0193] Comparative Example 2 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that an antistatic layer was not provided on the lubrication layer of the release coated film. The above-mentioned various physical properties of the obtained release film were evaluated, and as a result, as shown in Table 2B, the surface resistance value was poor, and therefore the unwinding static electricity was significantly poor.

[0194] Comparative Example 3 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that an antistatic layer-forming coating solution R10 having the following composition and not containing wax was applied onto the easy-slip layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0195] (Antistatic layer forming coating solution R10) Water 35.2 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.4 parts by mass Furthermore, the above-mentioned various physical properties of the obtained release film were evaluated, and as a result, as shown in Table 2B, the obtained film was significantly inferior in lubricity, abrasion resistance and particle shedding properties.

[0196] Comparative Example 4 A release layer forming coating solution M1 having the following composition was applied to one side of the laminated film F4 using reverse gravure so that the coating thickness after drying would be 20 nm. After that, the processing speed was adjusted so that the film entered the first drying oven 0.5 seconds later, and the film was continuously heated and dried at a first drying oven temperature of 90°C and a second drying oven temperature of 120°C. After the drying process, the film was irradiated on a cooling roll with an ultraviolet irradiator (Heraeus, H bulb) with an integrated light dose of 100 mJ / cm2. 2 The release layer was cured by irradiating it with ultraviolet light of 1000 nm.

[0197] A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R1 was applied to the other surface of the obtained release coated film by reverse gravure so that the coating thickness after drying would be 15 nm. As a result of evaluating the above-mentioned various physical properties of the obtained release film, a film with significantly poor slipperiness was obtained, as shown in Table 2B.

[0198] Comparative Example 5 A release layer forming coating solution M1 having the following composition was applied to one side of the laminated film F5 using reverse gravure so that the coating thickness after drying would be 20 nm. After that, the processing speed was adjusted so that the film entered the first drying oven 0.5 seconds later, and the film was continuously heated and dried at a first drying oven temperature of 90°C and a second drying oven temperature of 120°C. After the drying process, the film was irradiated on a cooling roll with an ultraviolet irradiator (Heraeus, H bulb) with an integrated light dose of 100 mJ / cm2. 2 The release layer was cured by irradiating it with ultraviolet light of 1000 nm.

[0199] A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R1 was applied to the other surface of the obtained release coated film by reverse gravure so that the coating amount after drying was 15 nm. As a result of evaluating the above-mentioned various physical properties of the obtained release film, many pinholes were generated during the coating of the ceramic slurry, as shown in Table 2B.

[0200] Comparative Example 6 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that no release layer was provided on the film planar layer. The above-mentioned various physical properties of the obtained release film were evaluated, and as a result, a film with significantly poor ceramic peeling force was obtained, as shown in Table 2B.

[0201] Comparative Example 7 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R11 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0202] (Antistatic layer forming coating solution R11) Water 34.6 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.4 parts by mass Silicone graft acrylic resin (Symac US-450, manufactured by Toagosei Co., Ltd.) 0.6 parts by mass The above-mentioned various physical properties of the obtained release film were evaluated, and as a result, a film with poor particle shedding properties was obtained, as shown in Table 2B.

[0203] Comparative Example 8 A release film for molding ceramic green sheets was obtained in the same manner as in Example 1, except that the antistatic layer-forming coating solution R12 having the following composition was applied onto the lubrication layer of the release coating film using reverse gravure so that the coating thickness after drying was 15 nm.

[0204] (Antistatic layer forming coating solution R12) Water 34.6 parts by mass Methanol 64.4 parts by mass Cationic antistatic agent (Elecond PQ-10, manufactured by Soken Chemical Industries, Ltd.) 0.4 parts by mass Polyether-modified polydimethylsiloxane (BYK-307, manufactured by BYK-Chemie Co., Ltd.) 0.6 parts by mass The above-mentioned various physical properties of the obtained release film were evaluated, and as a result, a film having an inferior surface resistivity after abrasion was obtained, as shown in Table 2B.

[0205] The various components used, their physical properties, etc. are shown in Tables 1A, 1B, 2A and 2B.

[0206] [Table 1A]

[0207] [Table 1B]

[0208] [Table 2A]

[0209] [Table 2B]

[0210] The invention of the embodiment satisfies the requirements of the present invention. As a result, for example, in a process of printing electrodes on a molded ceramic green sheet, when the surface of the release film opposite to the processing surface where the ceramic green sheet is provided contacts a support in a dryer and the sheet is transported with friction, it is possible to suppress charging due to friction.

[0211] The present invention can suppress the charge generation during transport, and therefore can suppress the inclusion of foreign matter due to charge generation caused by friction. Furthermore, the transportability is good, and the occurrence of poor winding and wrinkles in the film that may occur during film transport can be suppressed.

[0212] Furthermore, since the present invention has a good balance between good antistatic properties and winding properties, damage to the green sheet during molding of the thin layer region of the ceramic green sheet can be suppressed, and further, displacement of the printed electrodes can be suppressed.

[0213] In addition, the present invention can suppress not only the generation of charge when the ceramic green sheet is peeled off from the release film, but also the generation of charge during transportation.

[0214] Here, the present invention is excellent in adhesion between the substrate and the antistatic layer, and the antistatic layer can be prevented from falling off due to friction between the antistatic layer and the support in the dryer. In addition, it is possible to suppress process contamination caused by the antistatic resin falling off from the antistatic layer and the generation of pinholes in the green sheet, and it is also possible to solve new problems caused by the falling off of the antistatic resin. In particular, in the present invention, since the antistatic layer contains wax, a film that is excellent in suppressing particle falling off and has an excellent surface resistivity value after abrasion can be obtained.

[0215] On the other hand, in Comparative Example 1, the roughness of the two sides of the polyester film as the substrate was similarly large, so pinholes were generated in the ceramic green sheet. Comparative Example 2 did not have an antistatic layer, and for example, particle shedding properties and unwinding charging were poor. Comparative Example 3 did not have wax, and particle shedding properties were insufficient.

[0216] In Comparative Example 4, the roughness of the two sides of the polyester film substrate was similarly small, resulting in poor unwinding charging. In Comparative Example 5, the roughness of the AS side of the polyester film substrate was excessively large, resulting in the occurrence of many pinholes during the application of the ceramic slurry.

[0217] Comparative Example 6 did not have a release layer, and the ceramic releasability was poor, so sufficient evaluation was not possible. Comparative Example 7 did not contain wax in the antistatic layer, so a film with poor particle shedding properties was obtained. Comparative Example 8 did not contain wax in the antistatic layer, so a film with poor surface resistivity after abrasion was obtained. [Industrial Applicability]

[0218] The release film of the present invention can particularly suppress the occurrence of defects when molding a ceramic green sheet.

Claims

1. A release film for molding a ceramic green sheet, comprising a release layer, a polyester film as a substrate, and an antistatic layer in this order, The substrate has two surfaces with different roughnesses, the antistatic layer contains an antistatic resin and a wax, The average surface roughness (Sa1) of the release layer is less than 10 nm, and The area surface average roughness (Sa1) of the release layer and the area surface average roughness (Sa2) of the antistatic layer satisfy the following formula: 0.02<Sa1 / Sa2<0.5 Release film for molding ceramic green sheets.

2. 2. The release film for molding a ceramic green sheet according to claim 1, wherein the content of the wax is 1% by mass or more and 60% by mass or less relative to 100% by mass of a total solid content in the antistatic layer.

3. The release film for molding a ceramic green sheet according to claim 1 , wherein the wax comprises a polyolefin wax.

4. 2. The release film for molding ceramic green sheets according to claim 1, wherein the antistatic layer has a thickness of 0.005 to 0.1 μm.

5. 2. The release film for molding a ceramic green sheet according to claim 1, wherein the antistatic resin is an acrylic resin having a cationic functional group.

Citation Information

Patent Citations

  • Mold release film with ceramic sheet

    JP2002273715A

  • Release film roll for manufacturing thin ceramic sheet

    JP2003145685A

  • Mold release film roll

    JP2022128855A

  • Mold release film

    JP1998315373A

  • Carrier film for ceramic green sheet, ceramic green sheet processing method using it and manufacturing method of electronic part

    JP2006130724A